The politics of healthcare in Britain - Harrison, Stephen; McDonald, Ruth (Sage Publications, 2008)
`This is an excellent textbook for which there is currently a niche in the market. [It] will be invaluable to students of health policy, health studies and health service research′ - Professor Michael Calnan, University of Bristol Written by leading academics in their field this book provides a clear and considered overview of the politics of health care in Britain. Bringing together a wide range of material on both past events and recent developments, the chapters cover issues such as the politics of health professionalism, clinical knowledge and organisation and management. Each chapter offers a a unique combination of theory, historical detail and analysis of contemporary events. It features case studies to illustrate how policy has evolved and developed in recent years, and the implications these changes have for practice. Written in an accessible style the chapters also include comprehensive introductions, summaries and further reading sections.